2012
DOI: 10.1007/s00259-012-2213-x
|View full text |Cite
|
Sign up to set email alerts
|

Early prediction of survival following induction chemotherapy with DCF (docetaxel, cisplatin, 5-fluorouracil) using FDG PET/CT imaging in patients with locally advanced head and neck squamous cell carcinoma

Abstract: Early therapeutic response demonstrated on FDG PET/CT after two cycles of induction chemotherapy with DCF in patients with inoperable stage III/IV HNSCC seems to be a predictive factor for EFS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
42
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(45 citation statements)
references
References 37 publications
1
42
0
2
Order By: Relevance
“…This is in line with our findings in which no significant differences were seen in 18 F-FDG uptake between controls and irradiated mice at 1, 7 and 14 d after irradiation. Additionally, 18 F-FDG uptake can be influenced by local inflammation, complicating differentiation between the (residual) tumor and surrounding tissues (31). SCCNij167 tumors had an overall higher SUV max than SCCNij202 tumors, even though SCCNIj167 tumors are generally smaller and have a longer volume doubling time (14).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This is in line with our findings in which no significant differences were seen in 18 F-FDG uptake between controls and irradiated mice at 1, 7 and 14 d after irradiation. Additionally, 18 F-FDG uptake can be influenced by local inflammation, complicating differentiation between the (residual) tumor and surrounding tissues (31). SCCNij167 tumors had an overall higher SUV max than SCCNij202 tumors, even though SCCNIj167 tumors are generally smaller and have a longer volume doubling time (14).…”
Section: Discussionmentioning
confidence: 99%
“…2 and 3B). 18 F-FDG uptake (SUV mean and SUV max ) did not correlate to tumor volume or fEGFR (data not shown).…”
Section: Treatment Outcome and Imagingmentioning
confidence: 99%
See 2 more Smart Citations
“…The limited number of patients in this study, coupled with the generally favorable PET responses to induction chemotherapy, precluded our ability to detect a correlation between PET changes and long-term oncologic outcomes. In contrast, several prior studies showed that post-induction FDG-PET responses correlated with subsequent PET responses and PFS [28][29][30]. The utility of FLT-PET in assessing responses after induction chemotherapy in HNSCC has only been evaluated by a small number of studies.…”
Section: Discussionmentioning
confidence: 94%